ESTUDO DO RESÍDUO DE CEVADA COMO INIBIDOR DA CORROSÃO DE AÇO INOXIDÁVEL - Matos, Larissa Aparecida Corrêa (2018)
Steel is a metallic alloy of iron and carbon with industrial vast application. Stainless steel are one of the main iron alloys used due its high resistance to corrosive processes. Corrosion is defined as a material deterioration, metallic or not, generally by electrochemical processes. Corrosive processes occur naturally and cause economic and environmental damage, due to the substitution of metal parts and contamination by formed byproducts. Control and combat of corrosive processes can occur by process, medium or metal modification or by addition of protective coatings. Corrosion inhibitors are one of the main control methods of corrosive processes, by the addition of substances in low concentrations that help reduce or eliminate corrosion. The addition of corrosion inhibitors is facilitated because industrial modifications are not required; however, most of the currently used compounds for this purpose have high toxicity. Current studies aim diminish the use of synthetic compounds for natural ones. Natural compounds are a safe and environmental friendly source and may help the waste management. In this sense, this work aims to study the barley agro-industrial waste as a corrosion inhibitor for stainless steel in sulfuric acid. The agro-industrial waste was collected, dried, ground and characterized by scanning electron microscopy, elementary analysis and infrared spectroscopy. Different extraction methods were used to obtain the antioxidants from the agroindustrial waste. The acid extract was obtained from the waste dissolution directly in concentrated sulfuric acid; the aqueous extract, by the addition of waste in boiling water and posterior filtration, and the filtered was used to prepare the electrolyte; the basic extract was prepared by the addition of sodium hydroxide to the waste and posterior application in acid media. After six months of stocking, freeze-dried extracts were prepared to evaluate the waste biodegradability. The acid extract was prepared, neutralized and freeze-dried. The aqueous extract was separated in two fractions: the first was freeze-dried and the second was centrifuged in an ultrafiltration membrane to obtain the high molecular weigh fraction. All the extracts was analysed as corrosion inhibitors by gravimetric tests and electrochemical measures of open circuit potential (OCP), potentiodynamic polarization and electrochemical impedance spectroscopy (EIS). The morphology of the metallic surface was monitored by scanning electron microscopy after and before the extracts application to evaluation of the process inhibition. The results indicate that the selected waste have antioxidant composition and can be applied as a corrosion inhibitor. The gravimetric and electrochemical results indicate that the acid and aqueous extracts obtained immediately after the waste collect have 97.1% and 81.6% inhibition efficiency, respectively. The metallic morphology indicates that there is excellent antioxidant activity. The extracts acts mainly by physical adsorption onto the metallic surface. The waste loses its antioxidant properties with the stocking, which characterizes a biodegradable inhibitor. The barley agro-industrial waste is a promising substitute of organic conventional inhibitors, since it is easy to get and application and has great antioxidant activity.